Increasing Students' Learning Motivation in the Middle of the Covid-19 Pandemic - Imam Tabroni; Irma Mawaddah Nur (PT FORMOSA CENDEKIA GLOBAL, 2022)
Covid-19 pandemic causes precautionary measures by dismissing schools, especially in the red zone of the spread of Covid-19. In Regency Kotawaringin Timur is one of the red zones that requires schools from KB to universities to dismiss their students. This resulted in inhibition of the learning process. The teachers who usually teach in the classroom become confused in carrying out the learning process. One way that teachers do is to give assignments to students via via whatssap. But these efforts do not motivate students. This study aims to increase students’ learning motivation in learning Religious education Produktifisme with online methods using Google Classroom in class XII students of MA ALHUDA JATILUHUR in the academic year 2020/2021, in class XII SCIENCE 1 who took online classes via Google Classroom totaling 20 people. This research was conducted on 15 March, 2020 until May 15, 2020. The research method used was classroom action research. The study was conducted in one cycle consisting of four meetings. This research instrument was in the form of a Questionnaire Sheet for implementing Online Classes or Online Classes. Based on data analysis, the number of students who have high learning motivation is 15 people, and 5 student has the motivation to learn mathematics while online learning is done through Google classroom.